Room-temperature charge-to-spin conversion from quasi-2D electron gas at SrTiO₃-based interfaces - Shashank, Utkarsh (2023)
Interfacial two-dimensional electron gases (2DEG), especially the SrTiO3-based ones at the unexpected interface of insulators, have emerged to be promising candidates for efficient charge–spin interconversion. Herein, to gain insight into the mechanism of the charge–spin interconversion, quasi-2DEG between insulating SrTiO3 and two types of aluminum-based amorphous insulators, namely SrTiO3/AlN and SrTiO3/Al2O3, are focused on and their charge-to-spin conversion efficiency is estimated. The two types of amorphous insulators are selected to probe the overlooked contribution of oxygen vacancy. A mechanism to explain the results of spin–torque ferromagnetic resonance measurements is proposed and an analysis protocol to reliably estimate in quasi-2DEG is developed. The resultant, thickness of the 2DEG, is estimated to be 0.244 and 0.101 nm−1 for SrTiO3/AlN and SrTiO3/Al2O3, respectively, which are strikingly comparable to their crystalline counterparts. Furthermore, a large direct current modulation of resonance linewidth in SrTiO3/AlN samples is developed, confirming and attesting an oxygen vacancy-enabled charge–spin conversion. The findings emphasize the defects' contribution-, especially in oxide-based low-dimensional systems, and provide a way to create and enhance charge–spin interconversion via defect engineering.